When the United States and the People's Republic of China sneeze: International real and financial spillovers in Asia - John Beirne; Nuobu Renzhi; Ulrich Volz (Asian Development Bank Institute (ADBI), 2021)
This paper examines real and financial spillovers from monetary policy shocks originating in the US and the People's Republic of China (PRC) to advanced and emerging economies in Asia over the period 2000 to 2020. Using a structural panel vector autoregression approach, we find that Asian economies overall are more susceptible to spillovers to GDP, inflation, and the current account emanating from monetary policy shocks in the PRC than to those from the US. This is related to high inter-regional trade integration in Asia and is in line with previous research findings. However, while the prevailing literature has highlighted the dominant role of US monetary policy as a transmitter of shocks to global and Asian financial markets, we find more persistence in the response of advanced Asian interest rates to PRC monetary policy shocks. In addition, emerging Asian economies are found to be more susceptible to shocks emanating from the PRC in respect of equity markets and exchange rates. The rising synchronization of Asian financial markets in relation to the PRC as the financial account in the PRC has gradually opened as well as indirect effects via trade and regional value chains help to rationalize our findings.
Keywords: E44; E52; F33; F42; 330; monetary policy; global financial cycle; international spillovers; US; People's Republic of China